Bogidiella sinica sp.n. (Crustacea: Amphipoda) from southern China - Gordana Karaman; Boris Sket (Acta Biologica Slovenica, 1990)
Bogidiella sinica sp, n. is described and compared to other Asian species. Its most evident character is a very long antenna I. Its subgeneric position could not be established. It was found in karstic hypogean waters near Guilin in southern China, accompanied by other stygobitic Crustacea.